2017
DOI: 10.17712/nsj.2017.3.20160445
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric and neurological problems among Vitamin B12 deficient young vegetarians

Abstract: Objective:To assess the frequency of neuropsychiatric and neurological problems in apparently healthy young vegetarians and estimate serum Vitamin B12, methylmalonic acid (MMA), and folic acid levels.Methods:This prospective study was conducted in the Department of Biochemistry, Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Center (JPMC), Karachi, Pakistan, in the years of 2012 and 2013. The data of 100 vegetarians and 100 omnivores were analyzed and compared.Results:The serum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
(18 reference statements)
1
25
2
1
Order By: Relevance
“…Vitamin B 12 , or cobalamin, acts as a cofactor of the enzymes methionine synthase, acting in the conversion of homocysteine (Hcy) to methionine, and methylmalonyl-CoA mutase, that produces succinyl-CoA from methylmalonyl-CoA, the active form of methylmalonic acid (MMA) ( 6 ) . These reactions are involved in the methionine cycle and the folate cycle, both essential for DNA and RNA synthesis, erythropoiesis and the production of neurotransmitters ( 1 , 7 , 8 ) . Therefore, deficiencies of vitamin B 12 and folate can result in neurological damage, due to an inhibition of the formation of the myelin sheath, and megaloblastic anaemia ( 1 ) .…”
mentioning
confidence: 99%
“…Vitamin B 12 , or cobalamin, acts as a cofactor of the enzymes methionine synthase, acting in the conversion of homocysteine (Hcy) to methionine, and methylmalonyl-CoA mutase, that produces succinyl-CoA from methylmalonyl-CoA, the active form of methylmalonic acid (MMA) ( 6 ) . These reactions are involved in the methionine cycle and the folate cycle, both essential for DNA and RNA synthesis, erythropoiesis and the production of neurotransmitters ( 1 , 7 , 8 ) . Therefore, deficiencies of vitamin B 12 and folate can result in neurological damage, due to an inhibition of the formation of the myelin sheath, and megaloblastic anaemia ( 1 ) .…”
mentioning
confidence: 99%
“…Vitamin B12, in combination with folic acid, is known to reduce the levels of homocysteine, thereby reducing the toxic effects and thus improving the effect of anti-depressants by increasing the effectiveness of anti-depressants S-adenosylmethionine (SAMe) [30]. A study performed among the Indian population in 2017 demonstrated that Vitamin B12-deficient individuals, mostly vegetarians, were more prone to developing neurological problems [31]. Figure 3 illustrates the effects of Vitamin B12 deficiency on depression.…”
Section: Pathophysiology Of Depressionmentioning
confidence: 99%
“…The latter reports commonly refer to failure to thrive, hyperparathyroidism, macrocytic anemia, optic and other neuropathies, lethargy, degeneration of the spinal cord, cerebral atrophy, and other serious conditions. Although the direction of causality is not clear, meat avoidance is statistically associated with eating disorders and depression (Zhang et al, 2017;Barthels et al, 2018;Hibbeln et al, 2018;Matta et al, 2018;Nezlek et al, 2018) and may mirror neurological problems (Kapoor et al, 2017).…”
Section: Meat Avoidance Leads To a Loss Of Nutritional Robustnessmentioning
confidence: 99%